2011
DOI: 10.3920/wmj2010.1246
|View full text |Cite
|
Sign up to set email alerts
|

Climate change impacts on mycotoxin risks in US maize

Abstract: To ensure future food security, it is crucial to understand how potential climate change scenarios will affect agriculture. One key area of interest is how climatic factors, both in the near- and the long-term future, could affect fungal infection of crops and mycotoxin production by these fungi. The objective of this paper is to review the potential impact of climate change on three important mycotoxins that contaminate maize in the United States, and to highlight key research questions and approaches for und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(106 citation statements)
references
References 115 publications
1
97
0
2
Order By: Relevance
“…Also because mycotoxin concentrations show an extremely skewed distribution in foods and feeds, sampling variation across studies is common (Pitt et al, 2012). (Cotty et al, 1994;Wu et al, 2011). It has been suggested that an increase in temperature and rainfall may increase mycotoxin production for stored maize (Magan and Aldred, 2007;Sandris and Magan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Also because mycotoxin concentrations show an extremely skewed distribution in foods and feeds, sampling variation across studies is common (Pitt et al, 2012). (Cotty et al, 1994;Wu et al, 2011). It has been suggested that an increase in temperature and rainfall may increase mycotoxin production for stored maize (Magan and Aldred, 2007;Sandris and Magan, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although literature reviews on the expected impact from climate change on mycotoxin contamination of cereals and other crops are available (Magan et al, 2011;Marín et al, 2013;Marroquín-Cardona et al, 2014;Medina et al, 2014a,b;Miraglia et al, 2009;Ongoma, 2013;Lima, 2010, 2011;Paterson et al, 2014;Tirado et al, 2010;Wu et al, 2011), a limited number of studies quantitatively estimated these impacts. This study reviewed information from these quantitative studies, identified gaps in knowledge and data, and provided recommendations for future studies.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, los autores sugieren que el uso de líneas con alta resistencia a insectos y otras plagas, así como evitar la cosecha del maíz en etapas finales de desarrollo, puede disminuir el efecto de condiciones ambientales favorables para el desarrollo de fumonisinas y otras micotoxinas similares. Es también sensato tener en cuenta que, muy posiblemente, el cambio climático actual puede favorecer la contaminación con micotoxinas en cereales (Wu et al 2011;Van Asselt et al 2012), en países productores y exportadores, en los que hasta hace algunos años eso no sucedía (Miller 2008).…”
Section: Licencia Creative Commonsunclassified